Mastering American history - Groisser, Philip L. (New York : Oxford Book Company, 1977)
A history of the United States from European colonization to the early 1980's. A review test consisting of both objective and essay questions follows each chapter and unit.
Includes index.
900-999
Keywords: United States -- History -- Outlines, syllabi, etc; United States -- History -- Outlines, syllabi, etc; History